Masyarakat Adat dan Diskursus Representasi di Lingkar Artik: Tinjauan Kosmopolitanisme dan Geopolitik Kritis - Andy Fernanda Probotrianto (Universitas Airlangga, 2021)
The Arctic Circle, without a doubt, has turned into a region of various complexities and holds a huge prominence in the contemporary world; especially if one link it with discourses regarding energy, resources, and maritime issues which have helped in triggering wide international contestations. These discourses, consequently, are getting more proliferated as the polar ice melting. However, the existing paradigm carried about within the research of the region tends to be ignorant of those whom are marginalized, yet distinctly significant to the shaping of the Arctic environment, under the shadows of nation-states and high politics agendas: the indigenous peoples. This article, therefore, would contribute to the political discourse of the Arctic by elaborating the perspective of indigenous people in regards of the ongoing dynamics. Utilizing Critical Cosmopolitanism as a normative basis, as well as taking the approach offered by Critical Geopolitics, this writing will try to deconstruct how the nation state’s prolonged hegemony impacting the Arctic Circle, displaying the significance held by indigenous communities, as well as factors leading to its heighten representation—with a more through focus on Inuit Peoples in regard of their population and prominence within the discourse. This article reveals that the shifting global paradigm which, in time, echoing Cosmopolitanism values, such as inclusivity, paves a way to the growing representation to the indigenous peoples.